2005
DOI: 10.1097/00004872-200502000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial function and dysfunction. Part II: Association with cardiovascular risk factors and diseases. A statement by the Working Group on Endothelins and Endothelial Factors of the European Society of Hypertension*

Abstract: Dysfunction of the vascular endothelium is a hallmark of most conditions that are associated with atherosclerosis and is therefore held to be an early feature in atherogenesis. However, the mechanisms by which endothelial dysfunction occurs in smoking, dyslipidaemia, hyperhomocysteinaemia, diabetes mellitus, arterial hypertension, cerebrovascular diseases, coronary artery disease and heart failure are complex and heterogeneous. Recent data indicate that endothelial dysfunction is often associated with erectile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
516
4
28

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 694 publications
(558 citation statements)
references
References 161 publications
(125 reference statements)
10
516
4
28
Order By: Relevance
“…The mechanisms other than elevated BP, including endothelial dysfunction and arterial stiffness, are both involved in the pathogenesis of vascular disease. 7,35 Earlier, we have found that impaired endothelial function is associated with increased arterial stiffness. 13,14 Large artery stiffness causes a premature return of reflected waves in late systole, leading to increase in central pulse pressure, and thus systolic BP and load on the ventricle and oxygen demand.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The mechanisms other than elevated BP, including endothelial dysfunction and arterial stiffness, are both involved in the pathogenesis of vascular disease. 7,35 Earlier, we have found that impaired endothelial function is associated with increased arterial stiffness. 13,14 Large artery stiffness causes a premature return of reflected waves in late systole, leading to increase in central pulse pressure, and thus systolic BP and load on the ventricle and oxygen demand.…”
Section: Discussionmentioning
confidence: 97%
“…1,[7][8][9][10] We and others showed that endothelial function is involved in the regulation of arterial elasticity. [11][12][13][14] Our previous study, using brachial-ankle pulse wave velocity (baPWV) for artery elasticity and circulating endothelial microparticles (EMPs, defined as CD31 þ /CD42À MPs) for endothelial function assessment showed that the level of circulating EMPs was highly closed to baPWV in well-functional healthy subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, vascular aging is an independent risk factor of cardiovascular diseases that impair vascular health (Lakatta & Levy, 2003) and is now recognized as a target for intervention to achieve a healthier old age (Wang & Bennett, 2012). For that reason, understanding of the significance of age‐associated changes in the vascular endothelium is essential for the development of a therapeutic strategy to maintain vascular integrity (Brunner et al ., 2005). …”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] This could be attributed to the fact that both CAD and ED are characterized by endothelial dysfunction and injury. 11,12 These shared risk factors contribute to endothelial dysfunction and impede vasodilatation, thereby inhibiting the occurrence of normal erection.…”
Section: Introductionmentioning
confidence: 99%